Histomorphological analysis of the variability of the human skeleton: forensic implications - Cummaudo, Marco; Cappella, Annalisa; Biraghi, Miranda; Raffone, Caterina; Márquez-Grant, Nicholas; Cattaneo, Cristina (Springer, 2018)
One of the fundamental questions in forensic medicine and anthropology is whether or not a bone or bone fragment is human. Surprisingly at times for the extreme degradation of the bone (charred, old), DNA cannot be successfully performed and one must turn to other methods. Histological analysis at times can be proposed. However, the variability of a single human skeleton has never been tested. Forty-nine thin sections of long, flat, irregular and short bones were obtained from a well-preserved medieval adult human skeleton. A qualitative histomorphological analysis was performed in order to assess the presence of primary and secondary bone and the presence, absence and orientation of vascular canals. No histological sections exhibited woven or fibro-lamellar bone. Long bones showed a higher variability with an alternation within the same section of areas characterized by tightly packed secondary osteons and areas with scattered secondary osteons immersed in a lamellar matrix. Flat and irregular bones appeared to be characterized by a greater uniformity with scattered osteons in abundant interstitial lamellae. Some cases of “osteon banding” and “drifting osteons” were observed. Although Haversian bone represent the most frequent pattern, a histomorphological variability between different bones of the same individual, in different portions of the same bone, and in different parts of the same section has been observed. Therefore, the present study has highlighted the importance of extending research to whole skeletons without focusing only on single bones, in order to have a better understanding of the histological variability of both human and non-human bone.
Keywords: Forensic anthropology; Bone histology; Histomorphological variability; Human vs non-human